RETRACTED: Research of the production of gymnastics clothes for environmental protection - Rayimberdieva Dilrabo; Dadabayev Farhod; Turgunova Iroda; Yakubov Nosirjon; Muminov Bekzod (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001